Thermal Conductivity and Rheological Properties Improvements of Hydrogenated Oil-Based Drilling Fluid Through Nanoparticle Dispersion - CHAI, YEE HO (2017)
Current vegetable oil-based drilling fluid are inferior in terms of performance as compared against synthetic based drilling fluids. Addition of nanoparticles were proposed to overcome this challenge. In this study, graphene nanosheets, carbon nanotubes and graphene oxide nanoparticles were dispersed into hydrogenated oil-based fluid via two-step dispersion method which comprised of hydrodynamic cavitation and ultrasonication combination. Each nanoparticles were dispersed for three hours at three different concentrations of 25 ppm, 50 ppm and 100 ppm respectively. The effects of concentration on the physical properties of hydrogenated oil-based nanofluid were investigated. The physical properties, namely thermal conductivity and rheological behaviour, of the prepared nanofluids were measured. In addition, the effect of temperature on the thermal conductivity properties of nanofluid was investigated. It is found that thermal conductivity of nanofluid increased with respect to nanoparticle concentrations and temperatures with a maximum value of 14.41% enhancement using 100 ppm of graphene nanosheets at 50oC. The effective thermal conductivity of suspended graphene oxide calculated using “Nan et al. model” was found to be the highest at 5.60 ± 3.60 Wm-1K-1. The effect of shear rate and temperature on rheological behavior of nanofluids were investigated. Rheological analysis showed hydrogenated oil possesses Bingham fluid with shear thinning properties. The addition of nanoparticles do not alter the base fluid’s behavior although there is slight shear thickening behavior at higher shear rates. Findings showed higher nanoparticle concentration exhibited higher viscosity and shear stress although shear stress became independent to nanoparticle concentrations at higher temperature. Bingham model was able to predict consistently the experimental data compared to Power Law model. The stability of nanofluids was evaluated through visual observations in which the stability averaged up to six (6) days before full settlement. The average agglomerate size of suspended nanoparticle was calculated to be up to 1000 nm in radius.